PECULIARITIES OF THE REASONING OF JUDICIAL DECISIONS IN BRAZIL: THE NEW CIVIL PROCEDURE CODE - T. A. A. Wambier (BRICS Law Journal)
This paper deals with a relevant topic: the reasoning of a judicial decision as a requirement for its validity. In fact, this need is typical of democracies. In democracies, authorities have to justify their decisions which interfere in private lives. Decisions have to be reasoned also because they are, as a rule, appealable. What is challenged in an appeal is precisely the reasoning / motivation of judicial decisions.The main novelty in this context is a provision which exists in a Brazilian Bill for a new Civil Procedure Code, which determines how the decision must be reasoned. It openly recognizes that a judge bases his or her decision not only on statutes literally considered, but also on legal writing and on case law. The legislator was very bold, because we are a civil law jurisdiction, where students are currently led to believe the decisions emerge automatically from statutory law.Furthermore, this new provision teaches judges how to deal with all these elements, under penalty of having the decision being declared void or null.